The Influence of Lifestyle, Reference Group, and Attitude on Service Usage Decisions at Bio Live Health Home Sei Bamban - Nur Hazizah; Suhaila Husna Samosir; Melisa Zuriani Hasibuan; Emelia Rahmadany Putri Gami (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
This study was conducted at Bio Live Healthy Home, located in Sei Bamban District, Serdang Bedagai Regency. The primary objective of this research is to determine how lifestyle, reference groups, and consumer attitudes influence the decision to use services offered by the institution. In a rapidly growing health and wellness industry, understanding consumer behavior is essential to improve service quality and increase customer engagement. To achieve the research objectives, the study employed a survey method with a quantitative approach. The target population consisted of service users, and a sample of 92 respondents was selected. Data collection was carried out through a combination of observation, interviews, documentation, and the distribution of structured questionnaires. The questionnaire was designed to capture variables related to lifestyle, reference groups, attitudes, and service usage decisions. Before conducting the main analysis, the data were tested for validity and reliability to ensure that the instrument accurately measured what it intended to measure. Furthermore, classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests, were conducted to confirm the feasibility of using a multiple linear regression model. The analysis was performed using the Statistical Package for the Social Sciences (SPSS) software. The results of the study revealed that lifestyle, reference groups, and attitudes each had a significant and positive influence on the decision to use services at Bio Live Healthy Home. This indicates that individuals with health-conscious lifestyles, influenced by their social environment and holding positive attitudes toward wellness services, are more likely to engage with the services offered. Moreover, these three factors collectively contributed to a meaningful explanation of the variation in consumer decisions. In conclusion, the findings highlight the importance for service providers to consider psychological and social factors when designing marketing strategies.